Effectiveness of behavioural change interventions on physical activity, diet and body mass index of public primary healthcare users in Kosovo: the KOSCO cohort - Nicole Probst-Hensch; Sonja Merten; Katrina Ann Obas; Jana Gerold; Ariana Bytyçi-Katanolli; Naim Jerliu; Marek Kwiatkowski; Qamile Ramadani; Manfred Zahorka; Nicu Fota (BMJ Open, 2023)
Background Prevalent physical inactivity and poor nutrition contribute to high non-communicable disease (NCD) morbidity and mortality in Kosovo. To improve health services for patients with NCD the Accessible Quality Healthcare project developed behaviour change interventions following the principles of the WHO Package of Essential NCD (PEN) protocol. They were implemented into the public primary healthcare (PHC) system of five early-stage implementation municipalities (ESIM, 2018) and seven late-stage implementation municipalities (2020).Objective To assess the effect of the behaviour change interventions; motivational stages of behaviour change for physical activity and nutrition; and body mass index (BMI).Design Prospective cohort study.Data collection and analysis We included 891 public PHC users aged 40 years and above, who were enrolled in the KOSCO (Kosovo Non-Communicable Disease Cohort) cohort in 2019 and followed-up biannually until February 2021. The PHC users who consulted for themselves any health service were approached and recruited for cohort participation. Each participant contributed up to four self-reports of nutrition and physical activity, and up to three reports of motivation to change for a better lifestyle. These outcomes were modelled prospectively with robust mixed-effects Poisson regressions. The association between behaviour change interventions and BMI was quantified using linear regression.Results There was a high rate of smokers 20.5% and obesity 53.1%, and high rates of self-reported diagnoses of diabetes: 57.1%; hypertension 62.6%. We found no effect of residing in an ESIM, but adherence to both guidelines was higher in ESIM at the latest follow-up time point. ESIM residence was also associated with a twofold increase in the probability of reporting a high motivation for a better lifestyle and with a statistically non-significant decrease in BMI of −0.14 kg/m2 (95% CI: −0.46 to 0.19) at the latest follow-up.Conclusion The longitudinal results extend evidence on the effect of WHO PEN protocol in promoting physical activity and nutritional behaviour in the Kosovo context.